Reflections on dexmedetomidine as an optimum therapy for emergence delirium in the elderly with emergency abdominal surgery. Issue 3 (28th September 2021) - Zhou, Hong‐Su; Gu, Yue; Guan, Yi‐Huan; Liu, Fei
Abstract : Emergence delirium (ED) is a common complication in elderly patients in post post‐anesthesia care units (PACU), To our knowledge, there is currently no specific treatment for ED in the elderly, especially for patients combined with vital organs dysfunction. This article described an elderly patient with ED was successfully treated with dexmedetomidine. Although dexmedetomidine has been widely used in recent years, there are few articles on the administration of dexmedetomidine in PACU. The purpose of this paper is to review the literature and analyze related hazardous factors for ED in the elderly with complications of emergency abdominal surgery and angiocardiopathy, and to further confirm and explain the effectiveness and validation of dexmedetomidine as a rescue therapy in PACU. Finally, we look forward to more samples being collected to persuasively prove our opinion in this case.